1993
DOI: 10.1111/j.1460-2695.1993.tb00766.x
|View full text |Cite
|
Sign up to set email alerts
|

Effective Stresses and Microstructure in Cyclically Deformed 316l Austenitic Stainless Steel: Effect of Temperature and Nitrogen Content

Abstract: This paper reports a study on the factors influencing dislocation slip during cyclic deformation of 316L austenitic stainless steel. TEM investigations show that low temperature and interstitial nitrogen content favour planar slip and lead to higher erective stress values. Measurements of effective and internal stresses with the Handfield-Dickson technique indicate that the contribution of nitrogen in the effective component is more important than that of temperature. It is deduced that nitrogen acts through a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…Austenitic steels of type 316L (stacking-fault energy Ϸ 0.023 Jm Ϫ2 [7] ) are found to form spatial dislocation structures such as loop patches, PSBs, and cell structures after cycling at room temperature. [6,7,9,12] In this study of SDSS, only planar dislocation structures are observed in the austenite grains in the low-amplitude regime. Initialization of cross slip only occurs when the plastic-strain amplitude applied is high enough.…”
Section: The Csscmentioning
confidence: 91%
See 1 more Smart Citation
“…Austenitic steels of type 316L (stacking-fault energy Ϸ 0.023 Jm Ϫ2 [7] ) are found to form spatial dislocation structures such as loop patches, PSBs, and cell structures after cycling at room temperature. [6,7,9,12] In this study of SDSS, only planar dislocation structures are observed in the austenite grains in the low-amplitude regime. Initialization of cross slip only occurs when the plastic-strain amplitude applied is high enough.…”
Section: The Csscmentioning
confidence: 91%
“…The CSSCs of DSS were mainly ritic, and duplex stainless steels (DSS) has been discussed obtained at plastic-strain amplitudes lower than 10 Ϫ2 . in quite a few articles, [1][2][3][4][5]7,9,12,22,23] …”
Section: Introductionmentioning
confidence: 99%
“…Further examples of austenitic stainless steel microstructures formed at various deformation temperatures may be found in [10][11][12][13][14][15][16]. Figure 4 summarizes the temperature dependence of deformation-induced microstructural changes in austenitic steels.…”
Section: Relationship Between the Stacking Fault Energy (Sfe) And Defmentioning
confidence: 99%
“…Metastable austenitic stainless steels can be considered as TRIP (Transformation Induced Plasticity) steels because plastic deformation, either during forming or under service conditions, can lead to a strain-induced transformation from austenite to martensite [1]. Two types of martensite may form in austenitic stainless steels: ε and α'.…”
Section: Introductionmentioning
confidence: 99%